Atypical haemolytic uraemic syndrome in the eculizumab era: presentation, response to treatment and evaluation of an eculizumab withdrawal strategy. (27th March 2019) - Neave, Lucy; Gale, Daniel P.; Cheesman, Simon; Shah, Raakhee; Scully, Marie
Summary: The complement inhibitor, eculizumab, has revolutionised the management of atypical haemolytic uraemic syndrome (aHUS), although the optimum treatment duration is debated. Twenty‐two cases of acute aHUS managed with eculizumab were retrospectively reviewed, including outcomes after eculizumab withdrawal. Although 41% had an associated complement genetic abnormality, mutation status did not affect severity of clinical presentation. Sixty‐four percent required renal replacement acutely, with a high incidence of nephrotic range proteinuria (47%). Eculizumab followed a median of 6 days of plasma exchange. After a median duration of therapy of 11 weeks (range 1–227), haematological recovery was seen in 100%, while 81% achieved at least partial renal recovery (median increase in estimated glomerular filtration rate (eGFR) 49 ml/min/1·73 m 2 ). At median duration of follow‐up of 85 weeks (range 4–255), 54·5% had eGFR ≥ 60 ml/min/1·73 m 2, 27% had CKD, 14% were on dialysis, and 4·5% had died. Eculizumab was withdrawn in 59% (13/22) cases following complete haematological and renal recovery. Three of these 13 patients (23%) subsequently relapsed, with defined triggers in 2/3, but all made a full recovery with rapid resumption of eculizumab. There was a significant association between higher presenting creatinine and poorer renal outcomes. A strategy of eculizumab withdrawal in selected cases is both safe and cost effective.